Jumping in the Brazilian Women's Volleyball "B" Super-league - Kerkoski, M. J.; da Silva, L. H. M.; Hodeck, A.; Tuchel, J.; Hente, L. (Journal of Human Sport & Exercise, 2019)
The number of jumps during training and Volleyball games is directly related to knee injuries (Farina and Navarro 2008). Quantitative data with the jump magnitude serve to guide the training load (Berriel A, Foppa, G. 2004, Horta et al., 2007, Rocha and Barbanti 2007). There are no data on quantities and magnitudes of jumps in female athletes. The objective of this study was to verify the amount and magnitudes of jumps of setter, outside hitter and middle-blocker of a female team that played in the Brazilian B league of volleyball in training and competition. Participants of the case study were one setter, one middle-blocker and one outside hitter of the team. The accompaniment of each athlete was carried out during 5 training sessions and 2 games in the competition, including the final game. The jumps of the athletes were monitored with the equipment VERT Powered by G-VERT Technology. The results observed in training and competition, respectively, were: average number of jumps (147.2 / 134), average jump height (45.3 / 45.1), highest jump height (51.7 / 53) on the setter. The average jumps (71.8 / 95), average jump height (46.8 / 48), highest jump height (62 / 69.5) of the middle-blocker. The average number of jumps (64/116), average jump height (49.2 / 55.2), highest jump height (53.5 / 64.5) of the outside hitter. The jump means of the present study are higher than in previous studies, perhaps because of monitoring jumps of all athletes. The athlete who jumps most within the competition was the setter, followed by the outside hitter and finally the middle-blocker.